The home market effect, economic growth, and the dynamic trade patterns (2019)
In spite of increasing globalization, the effects of international trade on economic growth remain unclear. I consider an endogenous economic growth model in an open economy with the home market effect and non-homothetic preferences to identify the determinants of the various results in this relationship. The model shows how trade between similar countries leads to convergence in economic growth when knowledge spillovers are present, while trade between highly asymmetric countries produces divergence and may become trade in a poverty or growth trap. Besides, international trade does not necessarily imply greater welfare, as is usual in a static context under CES preferences.